2021
DOI: 10.1002/nau.24688
|View full text |Cite
|
Sign up to set email alerts
|

Urodynamic and clinical features in women with overactive bladder: When to suspect concomitant voiding dysfunction?

Abstract: The aim of this study is to describe the prevalence and type of female voiding dysfunction (FVD) in patients with overactive bladder (OAB) who were studied by urodynamics and its relationship with voiding symptoms.Methods: This is a cross-sectional study of female adult patients with OAB syndrome who underwent UDS in a University Hospital in Chile between January 2015 and April 2020. FVD was defined either as bladder outlet obstruction (BOO) or detrusor underactivity (DU). BOO was established if the Solomon-Gr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 25 publications
0
6
0
Order By: Relevance
“…The diagnosis of female bladder outlet obstruction is a matter of debate. 4,14,15 Multiple algorithms for diagnosis of female bladder outlet obstruction have been suggested, however none have been widely validated or accepted. The Blaivas criteria were used for diagnosis in this study as it has been shown to be accurate and reliable with over 90% of obstructed patients meeting criteria.…”
Section: Discussionmentioning
confidence: 99%
“…The diagnosis of female bladder outlet obstruction is a matter of debate. 4,14,15 Multiple algorithms for diagnosis of female bladder outlet obstruction have been suggested, however none have been widely validated or accepted. The Blaivas criteria were used for diagnosis in this study as it has been shown to be accurate and reliable with over 90% of obstructed patients meeting criteria.…”
Section: Discussionmentioning
confidence: 99%
“…BOO is more frequent than DU and should be suspected in patients with higher night-time frequency, presence of detrusor overactivity and a high post-void residual. Instead, DU should be suspected in patients with a smaller voided volume (8). Several combinations of nomograms were tested to increase the accuracy of diagnosing BOO and detrusor underactivity (DU) among women with LUTS (9).…”
Section: Discussionmentioning
confidence: 99%
“…Even up to one‐third of patients with overactive bladder (OAB) have been described to have concomitant voiding dysfunction in the form of either bladder outlet obstruction (BOO) or detrusor underactivity (DU) 1,2 . A recent report from our institution showed a prevalence of 23% of BOO and 3.3% of DU in OAB patients submitted to a urodynamic study (UDS) 3 …”
Section: Introductionmentioning
confidence: 99%
“…1,2 A recent report from our institution showed a prevalence of 23% of BOO and 3.3% of DU in OAB patients submitted to a urodynamic study (UDS). 3 It is well recognized that the goal of UDS (recreating a usual filling micturition cycle) has many obstacles. Besides the stress of being examined, the presence of urethral catheters has been broadly reported to influence the values of maximum flow rate during pressure-flow study (PFS).…”
Section: Introductionmentioning
confidence: 99%